Operational tolerance in intestinal transplantation. Issue 2 (30th August 2020) - Kroemer, Alexander; Khan, Khalid; Kaufman, Stuart S.; Kang, Jiman; Weiner, Joshua; Duttargi, Anju; Belyayev, Leonid; Ashokkumar, Chethan; Sindhi, Rakesh; Timofeeva, Olga A.; Zasloff, Michael; Matsumoto, Cal S.; et al.
Abstract : By presenting the first case report of true operational tolerance in an intestinal transplant patient, we aim to demonstrate that tolerance is possible in a field that has been hampered by suboptimal outcomes. Although operational tolerance has been achieved in liver and kidney transplantation, and some intestinal transplant patients have been able to decrease immunosuppression, this is the first instance of true operational tolerance after complete cessation of immunosuppression. A patient received a deceased‐donor small intestinal and colon allograft with standard immunosuppressive treatment, achieving excellent graft function after overcoming a graft‐versus‐host‐disease episode 5 months posttransplant. Four years later, against medical advice, the patient discontinued all immunosuppression. During follow‐up visits 2 and 3 years after cessation of immunosuppression, the patient exhibited normal graft function with full enteral autonomy and without histological or endoscopic signs of rejection. Mechanistic analysis demonstrated immune competence against third party antigen, with in vitro evidence of donor‐specific hyporesponsiveness in the absence of donor macrochimerism. This proof of principle case can stimulate future mechanistic studies on diagnostic and therapeutic strategies, for example, cellular therapy trials, that can lead to minimization or elimination of immunosuppression and, it is hoped, help revitalize the field of intestinal transplantation. Abstract : This unique case shows that operational tolerance is possible after intestinal transplantation, a field which has been hampered by suboptimal outcomes.